Exploring the nexus between economic complexity, economic growth and ecological footprint: Contextual evidences from Japan. (October 2021) - Ikram, Majid; Xia, Wanjun; Fareed, Zeeshan; Shahzad, Umer; Rafique, Muhammad Zahid
Graphical abstract: Highlights: This study investigates the impact of structural changes on ecological footprint. The quarterly data of Japan is studied from 1965Q1 to 2017Q4. ARDL and QARDL models are applied for impact detection. Cointegration exists between ECI, GDP, and EF both in short-run and long-run. ECI and GDP have asymmetric positive but decreasing impact on EF. The bi-directional causality exists between ECI, GDP, and EF in extreme quantiles. Abstract: This study investigates how structural changes and economic activities impact on the environment in Japan. Instead of using traditional economic and environmental factors, the authors used economic complexity and ecological footprint as key factors. Taking into account the dynamic nature of the relationship between economic activities and the environment, the recently developed Quantile ARDL (QARDL) model is employed. The results of the Quantile Granger-causality show bidirectional causality between economic growth, economic complexity, and ecological footprint in low and high quantiles. Likewise, QARDL findings reveal that there is asymmetric positive relation between economic growth and environment both in the short-run and long-run. Therefore, the long run cointegration and causality between economic complexity and ecological footprint suggest that policy efforts towards product diversification hold the potential to solve ecological problem.